Predicting the effects of EWOM and product innovation on purchase decision and the impact on customer loyalty - Putri, Alifa Savira; Indra, Ricardo; Pertiwi, Indah Dirgahayu Putri; Salsabilla, Ulfira (Edelweiss Applied Science and Technology, 2025)
Purpose: The dynamics of consumer behavior have undergone a transformative shift, especially in today’s digital age where most customers read online reviews before making purchase decisions. Online reviews are one example of the many examples of Electronic Word of Mouth (EWOM). However previous research states that not only does EWOM have an impact on purchasing decisions, but product innovation has also played a big role in purchasing decisions and purchase decision has an impact on customer loyalty. Therefore, this study aims to see how EWOM could affect purchase decisions by involving product innovation through online reviews of body care products Iswhite on the e-commerce Shopee. Research design, data, and methodology: This research adopts a positivist paradigm and employs a quantitative approach that is explanatory through a cross-sectional survey with 100 participants. The study utilizes theoretical approaches such as the Planned Behaviour Theory. After all the data was collected through Google Forms all the data was processed Statistical Package for Social Science (SPSS) software. Results: The result shows that the variables EWOM have an insignificant effect and the variables product innovation have a significant effect towards purchasing decisions and purchasing decisions has a significant effect towards on consumer loyalty. Conclusions: The results have shown that EWOM has an insignificant influence on purchasing decisions. Product innovation also has a significant influence on purchasing decisions and purchasing decision variables have a strong influence on consumer loyalty.